BOOK REVIEW ASIAN CONFLICT OF LAWS - EAST AND SOUTH EAST ASIA - Penasthika, Priskila Pratita (Indonesia Law Review, 2018)
Given the divergence of conflict of laws rules and recognition of foreign judicial decisions, a harmonized rules of conflict of laws is highly anticipated to improve legal certainty and cross-border commercial transactions. This book aims to provide a comprehensive overview of various approaches to conflict of laws of fourteen jurisdictions in East and South East Asia. It emphasizes that an understanding on the different frameworks toward conflict of laws in the region is necessary to encourage the harmonization attempts in the future. Corporate counsels, officials, policymakers, and other practitioners outside East and South East Asia are the intended readers of this book. Thus, the information specified in this book is also purposed to assist the ease of doing cross-border transactions inside and outside the region.